The relationship between the Arabic language and the law according to Jordanian legislation - الجدوع ناصر علي العطيوي; غنيمات اسماء مصطفى (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The Arabic language is one of the greatest, most difficult and most extensive languages in the world. This difficulty stems from the variety of its terminological and lexical stockpiles in which word can be interpreted into more than one meaning, a matter that is less common in all other languages. In addition, God Almighty has honored the Arabic language with the revelation of the Qur’an. Hence, the impact thereof appears in all fields and aspects of life such as: the political, social, economic, religious, scientific, and legal aspects. However, the focus of this research will be on the legal aspect, as The Jordanian legislator has given the Arabic language most attention thereof, either by stipulating it in the Jordanian constitution as an official language of the country, or by issuing a special law to protect it from infringement or violation. Moreover, the Arabic language has a prominent and essential role in the formulation legal texts and judicial rulings, proving the language’s positive impact on the legal articles’ texts’ coherency and clarity, consequently highlighting the prudence, strength, and effectiveness of the judicial rulings. Accordingly, this study aims to: firstly, clarify the relationship between the Arabic language and the law, and secondly, explicate the role of the Arabic language in drafting the legal texts. Methodologically, this research employs the inductive method in order to clarify the phenomenon under study, and form a perception of the facts through investigating societal changing processes related to the Arabic Language by exploring to which extent the law tackles negative and infringing phenomena, to eventually reach the desired results and recommendations of this study.